2021
DOI: 10.1002/cpt.2123
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Exposure Prediction Using Machine Learning

Abstract: The aim of this work is to estimate the area‐under the blood concentration curve of tacrolimus (TAC) following b.i.d. or q.d. dosing in organ transplant patients, using Xgboost machine learning (ML) models. A total of 4,997 and 1,452 TAC interdose area under the curves (AUCs) from patients on b.i.d. and q.d. TAC, sent to our Immunosuppressant Bayesian Dose Adjustment expert system (http://www.pharmaco.chu-limoges.fr/) for AUC estimation and dose recommendation based on TAC concentrations measured at least at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 17 publications
0
50
0
Order By: Relevance
“…Applications of ML to MIPD to date have found that ML models are often able to accurately estimate past drug exposure 24,25 , predict future drug exposure 26-28 or select doses [29][30][31][32] . However, the improvement in accuracy from these earlier approaches comes at the expense of pharmacological interpretability and the ability to simulate patient response to alternative dosing regimens 24,33,34 . An advantage of the combination of ML and PK models as described here is that clinical decision making is augmented by ML while maintaining the ability to forecast patient PK and extract mechanistic insight from PK parameter estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of ML to MIPD to date have found that ML models are often able to accurately estimate past drug exposure 24,25 , predict future drug exposure 26-28 or select doses [29][30][31][32] . However, the improvement in accuracy from these earlier approaches comes at the expense of pharmacological interpretability and the ability to simulate patient response to alternative dosing regimens 24,33,34 . An advantage of the combination of ML and PK models as described here is that clinical decision making is augmented by ML while maintaining the ability to forecast patient PK and extract mechanistic insight from PK parameter estimates.…”
Section: Discussionmentioning
confidence: 99%
“…10 The paper is a follow-up to a recent publication in the journal by the same group, on machine learning for the precision dosing of tacrolimus. 11 In both studies they used XGBoost, which stands for "Extreme Gradient Boosting, " an open-source software library with which large data sets are fit into a mathematical model, while maintaining high computational speed. Interestingly, the machine learning approach outperformed the PK model-informed method for the indications and times after transplant tested, and the authors are planning to implement the machine learning models as an expert system in the ISBA service.…”
Section: Machine Learning As a Novel Methods To Support Therapeutic Drug Management And Precision Dosingmentioning
confidence: 99%
“…[6][7][8][9][10][11] Machine learning (ML) is widely used in numerous applications, including pharmacology (PubMed Entry "Machine learning" & "Pharmacology" = 600 in 2018, 846 in 2019) especially in structure/activity predictions 12,13 or drug discovery 14 but only a few applications to predict drug exposure, PK parameters, or optimal dose exist. [15][16][17][18][19] Recently, we successfully applied a ML approach for tacrolimus AUC estimation that yielded better performance in terms of relative bias or imprecision vs. reference trapezoidal rule AUC than MAP-BE, even with only two samples. 19 We used extreme gradient boosting (Xgboost R package) where simple regression trees are iteratively built by finding among all the input variables, split values that minimize the prediction error.…”
Section: Mycophenolic Acid Exposure Prediction Using Machine Learningmentioning
confidence: 99%
“…[15][16][17][18][19] Recently, we successfully applied a ML approach for tacrolimus AUC estimation that yielded better performance in terms of relative bias or imprecision vs. reference trapezoidal rule AUC than MAP-BE, even with only two samples. 19 We used extreme gradient boosting (Xgboost R package) where simple regression trees are iteratively built by finding among all the input variables, split values that minimize the prediction error. The iterative process constructs an additional regression tree of the same structure that minimizes the residual errors of the previous regression tree.…”
Section: Mycophenolic Acid Exposure Prediction Using Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation